Data privacy for the smart grid - Herold, Rebecca; Hertzog, Christine (CRC Press, Taylor & Francis, 2015)
The Smart Grid is a convenient term to describe the modernization of electric, natural gas, and water grid infrastructures. The term encapsulates the convergence of remote monitoring and control technologies with communications technologies, renewables generation, and analytics capabilities so that previously non-communicative infrastructures like electricity grids can provide time-sensitive status updates and deliver situational awareness. While initially and mostly focused on electricity, many of the same technologies, particularly in information and communications technologies or ICT apply to natural gas and water grids. This book addresses privacy in all three of these consumables, but electricity occupies a unique place by virtue of the fact that we can produce it as well as consume it. In addition, existing technologies make it easier to get many more measurements about electricity than gas or water. These two unique qualities about electricity have very interesting ramifications for privacy, and therefore, this book will refer to electricity and electricity use cases because that provides the best framework for discussion of this important topic